McLuhan in the Digital Marketplace: Media Effects of Online Shopping - Gilchrist, Brian (Communications. Media. Design, 2018)
The digital marketplace functions as a medium that privileges nomos over phusis by reducing online shoppers to discarnate human beings and transforming goods and services into information. This interpretive article addresses how Marshall McLuhan’s approach to media ecology invites further analyses about the media effects of the digital marketplace. First, McLuhan’s media ecology is articulated to offer a theoretical frame for this article. Second, a brief summation of the Nomos-Phusis Debate announces how human beings use language to differentiate ideas from physical things. I suggest that McLuhan’s approach to media ecology contributes to the Nomos-Phusis Debate. Third, media effects on the human sensory experience from the ancient marketplace and contemporary brick-and-mortar stores are distinguished from the messages and massages of the digital marketplace. McLuhan’s media ecology challenges consumers to consider the effects of the digital marketplace as a medium, including unintended negative consequences, rather than just focusing on the digital marketplace’s positive messages.